Logiques du rapport sexuel - Norbert Campagna (Genre, Sexualité et Société)
What could entice one individual to have a sexual relation with another? The following article aims at answering this very question, apparently simple, while identifying different logics of sexual relationships. These logics range from free and unconditional gift to sexual exchange, as is paradigmatically practiced in prostitution. An adequate moral evaluation of prostitution will only be possible once it is placed in such a continuum; the major aim will then be to identify other examples of sexuality merchandizing outside this logic of exchange.